1980
DOI: 10.1210/endo-107-3-830
|View full text |Cite
|
Sign up to set email alerts
|

Intrathyroidally Generated Iodide: The Role of Propylthiouracil-Sensitive Processes in Its Production*

Abstract: Thyroid radioiodide to serum radioiodide concentration (*T/*S) ratios 1 h after 131I administration were 3 times higher in rats pretreated with propylthiouracil (PTU) than in rats with binding thyroids. Although indications of a preponderance of transported iodide in the thyroid early after 131I injection were found, a reduction of the 1-h *T/*S ratio in TSH-treated rats by the inhibitor of iodotyrosine dehalogenation, mononitrotyrosine, points to an early contribution of intrathyroidally generated (internal) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Whether PTU additionally affects thyroid uptake of iodine is not fully established in the literature. It has been suggested that PTU suppresses the formation of an inhibitor of iodide transport (Sherwin & Tong 1974;Halmi & Spirtos 1954) but a recent study failed to demonstrate any effect of PTU on thyroidal iodide uptake (Hildebrandt & Halmi 1980). We demonstrate that also during PTU influence, there is a marked accumulation in the thyroid of iodine as judged from the huge release in response to the subsequent TSH stimulation.…”
Section: Discussionsupporting
confidence: 48%
“…Whether PTU additionally affects thyroid uptake of iodine is not fully established in the literature. It has been suggested that PTU suppresses the formation of an inhibitor of iodide transport (Sherwin & Tong 1974;Halmi & Spirtos 1954) but a recent study failed to demonstrate any effect of PTU on thyroidal iodide uptake (Hildebrandt & Halmi 1980). We demonstrate that also during PTU influence, there is a marked accumulation in the thyroid of iodine as judged from the huge release in response to the subsequent TSH stimulation.…”
Section: Discussionsupporting
confidence: 48%